2007
DOI: 10.1111/j.1365-277x.2007.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and personal correlates of fruit and vegetable consumption in low income, urban Mexican children

Abstract: Correlates of fruit and vegetable consumption in children from Mexico City's State Schools were being female and accessibility to fruits and vegetables. Home and school environments are decisive for the children to increase FV consumption. Creative ways to encourage FV consumption in boys should be explored. These factors should be considered when designing programmes aimed at increasing consumption of fruits and vegetables in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
57
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 40 publications
0
57
2
5
Order By: Relevance
“…The percentage that reported consuming at least one portion of fruit or vegetables daily ranged from 91?5 % to 98?0 %. These levels are higher than those reported in nine European countries (8) and in Mexico (9) . Discrepancies between the countries may be because of the different measures used to assess FV consumption.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The percentage that reported consuming at least one portion of fruit or vegetables daily ranged from 91?5 % to 98?0 %. These levels are higher than those reported in nine European countries (8) and in Mexico (9) . Discrepancies between the countries may be because of the different measures used to assess FV consumption.…”
Section: Discussioncontrasting
confidence: 71%
“…The lack of gender differences in FV consumption may be partly explained by the fact that a wider age range of children participated in the present study (mean age ranged from 11?8 to 16?9 years), whereas previous studies were mainly conducted among elementary school students (7,9,10) . Whereas almost all adolescents in our sample consumed at least one portion of fruit or vegetables daily, only approximately one-fifth met the recommendation of consuming five or more portions daily.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These findings suggest that the mechanisms influencing changes in the consumption of these foods might be different (24)(25)(26) . They might also suggest the need to take into consideration the environmental context in which food consumption occurs in designing effective interventions (27)(28)(29) . Most of the participants in the current study were enrolled in the National School-feeding Programme.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover studies examining the effects of programmes designed to increase nutrition knowledge have found positive results (11,12) . However, other studies found no significant relationship (13,14) . Explanations for the inconsistent results are poor measurement of knowledge (lack of relevance, poor conceptualization, different levels of specificity of knowledge and dietary habits), different measurements of knowledge, poor measurement of dietary intake, lack of statistical power and the many factors that influence dietary behaviours of which nutritional knowledge is just one (15) .…”
mentioning
confidence: 83%